Islamic Banking: Concept and Future Potential in India (International Journal of Emerging Trends in Science and Technology, 2017)
Today that Islamic banking industry showing an average growth rate of 17%-20% annually and comprisesaround 400 institutions in 75 countries, with an asset under management ranging between US $1.66-2.1trillion, with expectations of market size to be $3.4 trillion by end of 2018 (Ernst & Young), according toStandard & Poor's Ratings Services the potential market is $4 trillion worldwide, therefore this can be atool for enhancing economic development in India. India is thriving, but Indians are not. With growingIslamic Banking and Indian socio-economic problems, this paper is going to find the growth of Islamicbanking worldwide and will try to find out how Islamic banking can provide great opportunities toinvigorate the Indian economy with the participation of previously excluded Muslims in Shariahcompliant banking and at the same time could lead to substantial inward investment to boost India'sfurther development. Furthermore it investigates the implementation of the Islamic banking system inIndia.